The Effect of Capital Adequacy, Liquidity and Cost Efficiency on Profitability: The Case of Private Banks and Foreign Banks Listed in Indonesian Stock Exchange - Sari, Ria Purnama; Djazuli, Abid; Choiriyah, choiriyah (International Journal of Finance Research, 2025)
This study aims to analyze the impact of increasing capital adequacy, high liquidity levels, and enhanced cost efficiency on the profitability of National Private Banks and Foreign Banks listed on the Indonesia Stock Exchange. There are three main problems faced by banks today. First, the management of credit distribution remains inadequate, which has the potential to increase the risk of bad debt. Second, the burden of regulation requires banks to set aside capital for additional bank capital reserves. Third, the entry of foreign banks into Indonesia is increasing, thereby tightening competition. These three problems will impact the condition of banking performance if improvements are not made in managing assets, credit, and costs by taking a sample of specific criteria from 20 banks using data from the period 2017 to 2023. This type of research is Quantitative. The variables used by researchers include Capital Adequacy, Liquidity, Cost Efficiency, and Profitability. The sample in this study is National Private Banks and Foreign Banks Listed on the Indonesia Stock Exchange. The data used in this study are secondary data collected using a documentation data collection method. The data analysis technique used is multiple linear regression. The results of this study show that (1) Capital Adequacy, Liquidity, and Cost Efficiency together have a positive and significant effect on profitability, (2) Capital Adequacy has no significant effect on profitability, Liquidity has no significant effect on profitability, and Cost Efficiency does not have a significant effect on profitability